2023
DOI: 10.1371/journal.pone.0286006
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic capital as effect modifiers of the association between psychosocial stress and oral health

Abstract: Objectives To assess the extent of the association of psychosocial stress with oral health in an Ontario population stratified by age groups, and whether any association is modified by indicators of social and economic capital. Methods We retrieved data of 21,320 Ontario adults, aged 30–74 years old, from the Canadian Community Health Survey (CCHS: 2017–2018), which is a Canada-wide, cross-sectional survey. Using binomial logistic regression models that adjusted for age, sex, education, and country of birth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
1
1
Order By: Relevance
“…The lack of association between social support networks and OHRQoL in this sample differs from the current literature that reports that social support networks contributes to better oral health 3 , 12 , 24 and also differs from a study that showed that social capital can reduce the effect of psychological stress on oral health 35 . People who have extensive social networks were also found to be more likely to report psychological well-being and positive OHRQoL 15 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of association between social support networks and OHRQoL in this sample differs from the current literature that reports that social support networks contributes to better oral health 3 , 12 , 24 and also differs from a study that showed that social capital can reduce the effect of psychological stress on oral health 35 . People who have extensive social networks were also found to be more likely to report psychological well-being and positive OHRQoL 15 .…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, it has been postulated that when two or more factors (e.g., psychological stress and support from social networks) affect a health condition (e.g., OHRQoL) by the same mechanism (e.g., health behaviors and missing teeth), they can interact by antagonism or synergy 33 , 34 : one factor can modify the effect of another ( Figure 1 ). Although plausible, the hypothesis that social support networks interact with discrimination and stress by antagonism has not yet been well investigated; previous studies with adults and schoolchildren have shown that indicators of social capital reduced the effect of perceived stress on oral health 35 and that the sense of coherence reduced the effect of perceived discrimination on quality of life 36 .…”
Section: Introductionmentioning
confidence: 99%
“…These results align with recent findings in the Canadian adult population demonstrating the role of social capital and SES in oral health (Hensel & Gomaa, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, oral health has also been found to associate with social capital, as have oral health related behaviours and access to dental care services (Campagnol et al, 2022;do Amaral Júnior et al, 2022). Recently, we have shown social capital to buffer the association between psychosocial stress and oral health in a large Canadian sample (Hensel & Gomaa, 2023).…”
Section: Introductionmentioning
confidence: 89%
“…Previous research has identified stress as a premorbid factor associated with many risk factors for chronic disease ( 82 , 83 ). Stress can stem from external events, such as major stressful life events or minor daily stressors, or from one's own perception of those experiences ( 84 ).…”
Section: Discussionmentioning
confidence: 99%